Agriculture productivity and level of agricultural development in Eastern Uttar Pradesh of the Middle Ganga Plain - Dinesh Kumar,; Kavita Mishra ,; Raj Bahadur , (National Geographical Journal of India, 2023)
Agriculture is the primary source of occupation for the Indian rural people who directly or indirectly depend on agriculture. Today, India is facing two most vital problems which is directly related to agriculture. The first one is to fulfil the growing demand of the ever-increasing population for food and other agricultural products, and the second is widespread disparities in agriculture development. This paper has attempted the measurement of agriculture productivity and the level of agricultural development in Eastern Uttar Pradesh of the Middle Ganga Plain.Taking into consideration this idea in mind, the present study attempts to calculate first the land productivity (per ha NSA) based on three indices viz. (i) Standardized crop Index(Isyi) (ii) Weight Crop Equivalent index (Iwei) and (iii) Cropping intensity index(Ici) and then labor productivity (per agricultural worker) with the help of agricultural worker index (Iewi). After this results here also calculate the level of agricultural development on the basis of 27 variables by the Z score method. The study area of Jaunpur is situated in Eastern Uttar Pradesh of the Middle Ganga Plain. The total area of the district is 4038 km2 having a population of 44, 94,204 persons. Several factors like water logging, salinity, relief variation, etc., and different modern agro-input have resulted in remarkable spatial disparity in agriculture productivity and level of development